Employability of graduates on the Public Service Internship Programme : the case study of the Limpopo Department of Economic Development, Environment & Tourism (LEDET), South Africa - Motene, Kgwadikatsoga Joseph (My University, 2017)
The Internship programme has been used by many governments and employers throughout the world to integrate academic theory learnt at schools and Universities and practiced in the workplace. The South African government introduced the Public Service Internship Programme(PSIP) in 2002, and one of its objectives was to reduce the high rate of graduates who are unemployable by appointing them as graduate interns for a period of 12 months, thus providing them with the public service skills and experience required by the Public Service in South Africa. The purpose of this study was to investigate the implementation of the Public Service Internship Programme with regards to its contribution to the employability of graduates: The case of the Limpopo Department of Economic Development, Environment, and Tourism in the Republic of South Africa. The study used the qualitative research method to interview 80 respondents ranging from Executive Management, Senior Management, Middle Management, Junior Management, Operational employees, Mentors and Graduate Interns to solicit their views and understanding on the implementation of the Public Service Internship Programme within the department. The study used content analysis to analyse data obtained from the 80 research respondents. The analysis was made using themes in line with thematic content analysis. The research findings confirmed that Graduate Interns are obtaining the necessary and relevant skills that will make them employable after completing the PSIP. The PSIP imparts Graduate Interns with skills that contribute to their employability in both the public and private sectors. It instils confidence and provides exposure and experience to Graduates Interns to have competitive advantages during job interviews in the public service and the private sector. It is a very useful programme that must be supported and encouraged in the public service as it assisted many to get jobs and reduce the rate of graduate unemployment in South Africa. It is relevant, useful and necessary to deal with the unemployment of graduates. It is successful and must be promoted because most Graduate Interns are employable during and after the completion of the programme. The study made the following recommendations; That all stakeholders must be inducted on PSIP to ensure its successful implementation, mentors must be trained on mentoring and coaching prior to their appointment, Mentoring vi be linked to the key result areas and key performance indicators of employees for it to be recognised in terms of the Performance Management and Development System, PSIP must be monitored and evaluated like all other government programmes, that the assignment of duties to graduates must be in line with their qualifications and their careers, graduate interns should be allowed to attend departmental meetings and functions as part of their learning areas, that those interning on the departmental Human Resources Management and Development be granted access to the PERSAL system as it is an important system in the South African Public Service, exit interviews must be conducted to get feedback from the interns on the implementation of the programme, and that proper allocation of offices or work spaces must be done by the department to enhance and improve the working conditions of the Graduate Interns
Thesis (MPA.) -- University of LImpopo, 2017
Keywords: Graduate interns; Graduate employability; Public service internship programme; Internship programs; Public service employment - Law and legislation